Experiments and competition policy - Hinloopen, Jeroen; Normann, Hans-Theo (Cambridge University Press, 2009)
Economists have begun to make much greater use of experimental methods in their research. The award of the Nobel Prize in 2002 to Vernon Smith confirmed that the use of such methods is now seen as an important and credible part of the economist's toolkit. In Experiments and Competition Policy, leading scholars in the field of experimental economics survey the use of experimental methods and show how they can help us to understand firm behaviour in relation to various forms of competition policy. Chapters are organized in terms of the main fields of competition policy - collusion, abusive practices and mergers - and there is also a separate section dealing with auctions and procurement. Written in a clear and non-technical style, this volume is an excellent introduction to what the increasingly important field of experimental economics can bring to the theory and practice of competition policy
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Wirtschaft; Competition; Economics / Experiments; Industrial policy; Experimentelle Wirtschaftsforschung; Wettbewerbspolitik; Aufsatzsammlung